Barriers and Facilitators in Preparation and Consumption of African Indigenous Vegetables: A Qualitative Exploration From Kenya - Merchant, Emily V.; Odendo, Martins; Ndinya, Christine; Nyabinda, Naman; Maiyo, Norah; Downs, Shauna; Hoffman, Daniel J.; Simon, James E. (Frontiers in Sustainable Food Systems, 2022)
Malnutrition and food security continue to be major concerns in sub-Saharan Africa (SSA). In Western Kenya, it is estimated that the double burden of malnutrition impacts 19% of adults and 13–17% of households. One potential solution to help address the concern is increased consumption of nutrient-dense African Indigenous Vegetables (AIVs). The objectives of this study were to: (i) document current methods used for preparation and consumption of AIVs; (ii) identify barriers and facilitators of AIVs consumption and preparation; and (iii) identify a package of interventions to increase the consumption of AIVs to promote healthy diets. This study used qualitative data collected from 145 individual farmers (78 female and 67 male) in 14 focus group discussions (FGDs) using a semi-structured survey instrument. Most farmers reported that they prepared AIVs using the traditional method of boiling and/or pan-cooking with oil, tomato, and onion. However, there were large discrepancies between reported cooking times, with some as little as 1–5 min and others as long as 2 h. This is of importance as longer cooking times may decrease the overall nutritional quality of the final dish. In addition, there were seasonal differences in the reported barriers and facilitators relative to the preparation and consumption of AIVs implying that the barriers are situational and could be modified through context-specific interventions delivered seasonally to help mitigate such barriers. Key barriers were lack of availability and limited affordability, due to an increase cost, of AIVs during the dry season, poor taste and monotonous diets, and perceived negative health outcomes (e.g., ulcers, skin rashes). Key facilitators included availability and affordability during peak-season and particularly when self-produced, ease of preparation, and beneficial health attributes (e.g., build blood, contains vitamins and minerals). To promote healthy diets within at risk-populations in Western Kenya, the findings suggest several interventions to promote the preparation and consumption of AIVs. These include improved household production to subsequently improve affordability and availability of AIVs, improved cooking methods and recipes that excite the family members to consume these dishes with AIVs, and the promotion of the beneficial heath attributes of AIVs while actively dispelling any perceived negative health consequences of their consumption.